Systematic literature review on evaluation models and methods in enterprise architecture research - Khairina, Dyna Marisa; Purwanto, Purwanto; Kusumo Nugraheni, Dinar Mutiara (Institute of Advanced Engineering and Science, 2024)
Several enterprises implemented enterprise architecture (EA) projects to align business and information technology (IT) strategies. The evaluation process is needed to ensure the implementation of EA projects provides effectiveness, efficiency, and feasibility of EA information systems (IS) and assesses previous project experience to avoid future EA project risks. The study aims to present a systematic literature review (SLR) of the models and evaluation methods used or developed, especially in the field of EA research. Based on the inclusion and exclusion criteria, 21 articles were selected for review. The results of the study present an overview of the models and methods used as well as new approaches developed for EA evaluation as well as information based on approaches related to models and methods identified as organizing information and data analysis to broaden future research insights. The literature review also provides additional simple theories related to the implications and techniques of the identified models and methods. The study contributes to company stakeholders to encourage the implementation of EA, identify improvements and enhancements to EA projects as well as further references and insights for practitioners and researchers regarding EA evaluation as an effort to assess the success of achieving enterprise goals.